Menggali Kearifan Lokal Nusantara: Sebuah Kajian Filsafati - Sartini Sartini (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2004)
Local genius is local ideas that is characterized such as: wise, full of wisdom, good values, that planted and followed by society. Local genius is also a local wisdom. It stands from the outer culture, that accommodate and intergrate the outer culture into inside and give them the right way. Local genius emerge into: value norm, faith custom, etc. They have special meaning and function. It must be changed because of cross culture and globalization. It gives a challenge to explore and criticize it in scientific ways.